Transplantation of gastric epithelial mitochondria into human gastric cancer cells inhibits tumor growth and enhances chemosensitivity by reducing cancer stemness and modulating gastric cancer metabolism - Hsin-Yi Tsai; Kuen-Jang Tsai; Deng-Chyang Wu; Yaw-Bin Huang; Ming-Wei Lin (Stem Cell Research & Therapy)
Abstract Background Gastric cancer is the malignant disease. The problems associated with cancer stemness and chemotherapy resistance in gastric cancer therapy remain unresolved. Glucose-regulated protein 78 (GRP78) is a biomarker of gastric cancer and modulates cancer stemness and chemoresistance. Previous studies have shown that mitochondrial transplantation from healthy cells is a promising method for treating various diseases and that the regulation of mitochondrial metabolism is crucial for modulating the stemness and chemoresistance of cancer cells. The aim of this study was to investigate the therapeutic effect of mitochondrial transplantation from normal gastric epithelial cells into gastric cancer and the associated mechanisms. Methods The expression of cancer stemness markers, intracellular oxidative stress, or apoptotic-related proteins were evaluated via flow cytometry. Western blotting was used to investigate the molecular mechanism involved in MKN45 or AGS human gastric cancer cells after transplantation with human gastric epithelial mitochondria. The mitochondrial metabolic function of gastric cancer cells was determined via a Seahorse bioanalyzer, and extracellular lactate was evaluated via bioluminescent assay. The viability of 5-fluorouracil (5-FU)-treated gastric cancer cells was detected via a CCK-8 assay. Furthermore, a xenograft tumor animal study was performed to validate the therapeutic effects of human gastric epithelial mitochondrial transplantation in gastric cancer. Immunohistochemistry and Western blotting were then used to assess the expressions related to cancer stemness and mitochondrial metabolism-related proteins in tumor tissues. Results Transplanting human gastric epithelial mitochondria downregulates gastric cancer mitochondrial biogenesis, glycolysis, GRP78-mediated cancer stemness, and increases oxidative stress, cell apoptosis under hypoxic conditions and chemosensitivity in response to 5-FU treatment. Moreover, the transplantation of epithelial mitochondria into gastric tumors inhibited the tumor growth in vivo tumor graft animal models. Therefore, mitochondrial transplantation can be considered for the treatment of gastric cancer.